2021
DOI: 10.3390/antiox10081311
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Endothelial NOX5 Alters the Integrity of the Blood-Brain Barrier and Causes Loss of Memory in Aging Mice

Abstract: Blood-Brain barrier (BBB) disruption is a hallmark of central nervous system (CNS) dysfunction, and oxidative stress is one of the molecular mechanisms that may underlie this process. NADPH oxidases (NOX) are involved in oxidative stress-mediated vascular dysfunction and participate in the pathophysiology of its target organs. The NADPH oxidase 5 (NOX5) isoform is absent in rodents, and although little is known about the role it may play in disrupting the BBB, it has recently been implicated in experimental st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…For this study, an endothelial NOX5-β conditional knock-in mice was employed (Nox5 +/− /Cre +/− ). Seven-week-old male mice expressing endothelial-specific CRE recombinase (Cdh5(PAC)-CreERT2; CRE +/− ) were employed as a control group [ 24 , 25 ]. NOX5-β endothelial expression was only detectable after intraperitoneal administration of tamoxifen (40 mg/kg) on 3 non-consecutive days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this study, an endothelial NOX5-β conditional knock-in mice was employed (Nox5 +/− /Cre +/− ). Seven-week-old male mice expressing endothelial-specific CRE recombinase (Cdh5(PAC)-CreERT2; CRE +/− ) were employed as a control group [ 24 , 25 ]. NOX5-β endothelial expression was only detectable after intraperitoneal administration of tamoxifen (40 mg/kg) on 3 non-consecutive days.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, the purpose of this study was to analyze whether endothelial NOX5 expression in mice fed with a high-fat diet (HFD) could have an effect on thermogenesis activation and lipolysis in the adipose tissue and characterize the molecular mechanisms involved. With that objective, a conditional knock-in mice model expressing NOX5 in the endothelium was used [ 25 ]. The principal findings of this work reveal that endothelial expression of NOX5 in mice fed with HFD promotes thermogenesis activation and lipolysis in adipose tissue.…”
Section: Introductionmentioning
confidence: 99%
“…In a different study, using a knock-in system in which Nox5 is only expressed in endothelial cells, a positive correlation between Nox5 expression and TJ degradation was demonstrated. While no differences in blood pressure or locomotor activity were observed, chronic Nox5 expression induced Cox2 upregulation in the brain and induced cognitive deficits in knock-in aged mice [ 54 ].…”
Section: Nox Proteins In Cns Signal Transductionmentioning
confidence: 99%
“…In this sense, growing evidence points to NADPH oxidase activity, and more specifically that of NOX5, as a key player in endothelial dysfunction. Using a conditional knock-in NOX5 mouse model, Cortes et al [ 2 ] investigate its role in promoting ageing-related vascular alterations that lead to blood–brain barrier (BBB) damage and cognitive impairment. Even with no blood pressure effect, the authors observed that aged mice expressing NOX5 in their endothelium present reduced tight-junction protein expression, which is accompanied by the poor performance of memory tests, suggesting that vascular NOX5 may favour behavioural changes in ageing through alteration in the BBB by oxidative stress.…”
mentioning
confidence: 99%